The Emergence of Professional-Emotional Burnout Syndrome in Teachers of Preschool Education Institutions: Factors, Symptoms, Stages, and Prevention - Iryna Skomorovska; Natalia Kyrsta; Marianna Matishak (Vasyl Stefanyk Precarpathian National University, 2023)
The article is devoted to the problem of the syndrome of professional and emotional burnout of teachers. The authors analyzed the main factors, indicated the symptoms of professional burnout, and established methods and means of prevention of emotional burnout in the teaching profession. The article describes the content of key concepts, the essence of the categories «emotional burnout», «stress», and «emotional exhaustion», and the emergence and understanding of related concepts in the scientific research of foreign scientists (A. Griffiths, S. Jackson, T. Kox, K. Maslach, H. Selye, H. Freudenberg, etc.). The results of the analysis of scientific works proved that stress has three stages of development: anxiety, resistance, and exhaustion, which can cause professional and emotional burnout in specialists in various fields. The basic symptoms are emotional exhaustion, depersonalization, and reduction of personal achievements. T. Cox and A. Griffiths (about 150) provided a more detailed analysis of the symptoms of professional and emotional burnout and distinguished three groups of symptoms - affective, cognitive, and motivational. The peculiarities of the raised problem in our country are revealed, taking into account the specifics of the teaching profession. The factors of professional burnout of preschool teachers are singled out, namely: high responsibility, daily mental overload, the excessive number of duties, high emotional inclusion, strict control of the administration, etc. Measures to prevent emotional burnout were presented in three aspects: professional and administrative (psycho-training, role-playing, business games, mentoring, a favorable psychological climate in the team, etc.), non-professional (a rational division of work and rest, healthy nutrition, physical exercises, self-regulation, establishing short-term and long-term goals, etc.). It has been established that a comprehensive approach to the prevention of professional burnout in preschool teachers should include correction of the mental, physical, and spiritual components of the individual's health.